2004
DOI: 10.1097/01.asn.0000103225.68136.e6
|View full text |Cite
|
Sign up to set email alerts
|

Activin A Is a Potent Activator of Renal Interstitial Fibroblasts

Abstract: Abstract. The present study was conducted to examine the involvement of the activin-follistatin system in the fibrotic process of the kidney. Immunoreactive activin A was upregulated in tubular cells in the kidneys with unilateral ureteral obstruction but not in normal and contralateral kidneys. Activin A promoted cell proliferation, enhanced the expression of type I collagen mRNA, and induced the production of ␣-smooth muscle actin in a rat kidney fibroblast cell line (NRK-49F cells) as well as in primary cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 52 publications
5
110
1
4
Order By: Relevance
“…This is consistent with the effects of other members of the TGF-b family such as activin and TGF-b1 in various tissues (Wada et al 2004, Yamashita et al 2004, Verrechia et al 2006. Using the multipotent mesenchymal embryonic C3H10T1/2 cell line, it was possible in our J N ARTAZA and others .…”
Section: Discussionsupporting
confidence: 74%
“…This is consistent with the effects of other members of the TGF-b family such as activin and TGF-b1 in various tissues (Wada et al 2004, Yamashita et al 2004, Verrechia et al 2006. Using the multipotent mesenchymal embryonic C3H10T1/2 cell line, it was possible in our J N ARTAZA and others .…”
Section: Discussionsupporting
confidence: 74%
“…However, previous studies have shown that activin A is capable of causing an increase in the proliferation of human lung fibroblasts (Heeren et al 2015) as well as promoting proliferation of cultured rat renal interstitial fibroblasts and increasing the expression of type I collagen (Yamashita et al 2004). We have observed that activin A did not affect the expression of FBN1 or FBN2 or the other TGFβ-associated genes examined in our human samples.…”
Section: Discussionmentioning
confidence: 47%
“…HUVEC were cultured in HuMedia-EB2 supplemented with HuMedia-EG for 48 h, and HUVEC-derived conditioned media (HUVEC-CM) were collected. Protein extraction was performed as described previously (36). Human Matrix Metalloproteinase Antibody Array I (Raybiotech, Norcross, GA) was used according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%